RESOURCE EFFICIENCY EVALUATION IN FLIGHT CONTROL SIMULATOR DESIGN: A MULTI-FRAMEWORK SYSTEMATIC LITERATURE REVIEW - Ekanesti Ruswidia Sari; Heriana (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This article presents a systematic literature review (SLR) of resource efficiency evaluation strategies in the design and development of flight control simulators for combat aircraft, integrating perspectives from Resource Efficiency Theory, Lean Manufacturing, System Dynamics, Optimization, Benchmarking, and Green Engineering. Peer-reviewed publications and industry reports from 2020–2025 were synthesized using PRISMA guidelines. To enhance reproducibility, selection criteria were refined to include studies with empirical results (e.g., quantitative metrics like percentage reductions in time, cost, or energy with reported statistical significance or sample sizes) and/or detailed methodological contributions (e.g., novel algorithms or frameworks with validation). Results indicate that modular frameworks, value stream mapping, dynamic simulation modeling, multi-objective optimization, industrial benchmarking, and sustainable engineering practices have enabled reductions in development time by up to 45%, cost by 30%, and energy consumption by up to 97%. The study highlights continuous improvement, empirical benchmarking, AI integration, and sustainability as essential themes for future research and industrial implementation in flight control simulator development.